“When the Saints Go Marching in”: Gregory of Tours and his domestic Oratory - Greschat, Katharina (Archiv für Religionsgeschichte, 2017)
In the Glory to the Confessors 20 Gregory of Tours describes how he establishes an oratory for the veneration of the relics of Martin of Tours, Julian of Brioude, Saturninus of Toulouse, and Illidius of Clermont in his own house. This paper will show that Gregory does not only establish his personal relic cult in honor of members of his family or their patron saints to promote his family and himself, but that he uses elements of the Roman domestic cult together with the ceremonies of dedication and adventus of the saints in order to demonstrate that he is the rightful bishop of Tours and a powerful aristocratic leader of his civitas.